Representation of warm conveyor belts in sub-seasonal forecast models and the link to Atlantic-European weather regimes - Wandel, Jan Lucas (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2023)
This study systematically investigates the representation of warm conveyor belts (WCBs) in large reforecast data sets of different numerical weather prediction models and evaluates the role of WCBs for the onset and life cycle of Atlantic-European weather regimes. The results emphasize the importance of accurate forecast of WCBs for sub-seasonal prediction on time scales beyond two weeks and tie the low forecast skill of blocked weather regimes over Europe to misrepresented WCBs.